Mobility models for an asynchronous wireless sensor multimedia network - Kumar D, Praveen; Jerritta S, Dr (International Journal of Engineering and Technology, 2018)
In Wireless Sensor Multimedia Networks, the movement models and tracking mechanisms have important roles on Quality of data collection and network delay. The various movement models in a hierarchically connected network entities are discussed in a Wild life Habitat moni-toring scenario. The quality of routing decisions depends on how accurately we can predict the mobility pattern of nodes. A simulator test-ing the different mobility models is discussed in this paper.Â Â